2015
DOI: 10.1590/0103-8478cr20131676
|View full text |Cite
|
Sign up to set email alerts
|

Adubação boratada e produção de sementes de trigo

Abstract: RESUMO A deficiência de B pode diminuir a fertilidade das flores, prejudicando a produtividade de sementes de trigo. O trabalho objetivou avaliar a produção e a qualidade fisiológica de ABSTRACT Boron deficiency can decrease fertility of flowers, harming productivity of wheat seeds. The experiment was conducted in didactic laboratory seed testing and in the greenhouse, both located in the municipality of Capão do Leão (RS). The objective of this study was to evaluate the production and physiological quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
7
1
5
Order By: Relevance
“…Debnath et al (2011) found a higher yield of wheat grain at a dose of 1.9 kg ha -1 B. However, Brunes et al (2015) verified that boron fertilization, applied at sowing or tillering in doses between 2.5 and 3.0 kg ha -1 caused an increase in the number of seeds and spikes per plant, but with a reduction of seed yield per plant, mass of 1000 seeds and the hectoliter mass, unlike the one verified in the present work. However, a drastic reduction of grain yield was observed above the dose of 2.8 kg ha -1 of B.…”
Section: Discussioncontrasting
confidence: 59%
“…Debnath et al (2011) found a higher yield of wheat grain at a dose of 1.9 kg ha -1 B. However, Brunes et al (2015) verified that boron fertilization, applied at sowing or tillering in doses between 2.5 and 3.0 kg ha -1 caused an increase in the number of seeds and spikes per plant, but with a reduction of seed yield per plant, mass of 1000 seeds and the hectoliter mass, unlike the one verified in the present work. However, a drastic reduction of grain yield was observed above the dose of 2.8 kg ha -1 of B.…”
Section: Discussioncontrasting
confidence: 59%
“…These results may be explained mainly by the low B requirement of the used corn hybrid, besides the high soil clay content, which could increase the adsorption of this element. Trautmann et al (2014) also did not find B influence on soybean grain yield, although other reports highlight the importance of B on reproductive development of crops (DEBNATH et al, 2011;MUHMOOD et al, 2014;BRUNES et al, 2015). Yet, Adiloglu and Adiloglu (2006) verified that shoot dry matter yield of corn plants grown in Zn-deficient soil decreased with B application, while increased with Zn application soil.…”
Section: Leaf Micronutrient Concentrations and Corn Grain Yieldmentioning
confidence: 84%
“…Muhmood et al (2014) researched the borate fertilization of wheat and obtained a higher grain yield at a dose of 2 kg ha -1 and Debnath et al (2011) found a higher yield of wheat grain at a B dose of 1.9 kg ha -1 . However, Brunes et al (2015) found that borated fertilization applied at sowing or tillering in doses between 2.5 and 3.0 kg ha -1 caused an increase in the number of seeds and spikes produced per plant. However, there was a reduction in the seed yield per plant, the mass of 1000 seeds, and the hectoliter mass.…”
Section: Resultsmentioning
confidence: 96%